Clinical and Mathematical Model for Predicting the Effectiveness of Physical Rehabilitation in Adolescents with Hypertension - Ye.V. Nedelska (Zaslavsky O.Yu., 2016)
The article deals with the method for predicting the effectiveness of physical rehabilitation in adolescents with hypertension. This disease has an onset in adolescence and leads to the formation of hypertension in adults with a high risk of cardiocerebral complications that determines disability and mortality of adult population. This article describes the ROC-analysis of obtained clinical and experimental data, which revealed the important prognostic properties of specific clinical parameters in adolescents with hypertension - students of Zaporizhzhia State Medical University.